From Knowledge to Ontological Awakening: Thinking Nature as Relatedness - Malette, Sebastian (The Trumpeter, 2012)
In this paper, I examine the ontological valuation of what-stands-on-its-own in relation to the problem of thinking Nature beyond empirical reductionism and conceptual solipsism. Exploring the roots of this ontological valuation in Hellenistic philosophy, and its subsequent repositioning within the Christian doctrine of Creation, I suggest that the emergence of an externalist ontology has facilitated the rise of a paradigm of knowledge gradually discarding ontological or metaphysical objects of knowledge (such as Nature) because non-amenable to the criteria of functionalism and empirical fallibilism. I conclude this paper by suggesting that a relational ontology may offer an alternative to formulate an expression of Nature that can better resonate with our ecological findings in terms of ontological interdependency and interrelatedness, while avoiding the peril of both essentialism, reductionism and solipsism when it comes to thinking Nature.